Functional and in silico Characterization of Neutralizing Interactions Between Antibodies and the Foot-and-Mouth Disease Virus Immunodominant Antigenic Site - Marrero Diaz de Villegas, Ruben; Seki, Cristina; Mattion, Nora M.; König, Guido A. (Frontiers in Veterinary Science, 2021)
Foot-and-mouth disease, FMD, is one of the major animal diseases affecting many domestic and wild cloven-hoofed species, and it is caused by a picornavirus, the FMD virus (FMDV). The host control mechanism is mainly exerted by neutralizing antibodies that recognize pathogen-relevant regions. Specifically, the major target for neutralizing antibodies lays in the core of the viral recognition site for its mayor host receptor, integrins. Currently, we have evaluated the effectiveness of multiple computational programs with different physical-chemical simplifications to model and predict the recognition phenomena between the main FMDV-serotype C antigen (site A) and monoclonal antibodies, and their variation facing the virus evolution through mutational changes. The emerging data from these experiments showed a good correlation with previously published experimental data and predictions, supporting the feasibility of using computational methods based on the side chain optimizations and the use of an ensemble of interaction complexes. We also cloned the coding sequence of two novel monoclonal antibodies obtained in Argentina that recognize and neutralize site A epitopes, mainly from FMDV of serotype A. For these antibodies, we implemented a protocol for modeling their molecular structure as well as their interaction with viral antigen, assisted by the information of the mutational profiles developed in a peptide ELISA tests. By doing so, we developed a differential and fine map of the functional epitope for those antibodies. This work demonstrates the relevance and applicability of the computational prediction techniques on molecular structure modeling and molecular docking in the interaction phenomena between the FMDV immunodominant site A and a biotechnologically relevant host molecule, the antibody.